Decadal Analysis of the Efficiency and Degradation of a Photovoltaic Plant in a Semi-Arid Region - Rubens Silva de Sena, Nicolas; Vieira, Romênia (Latin American Journal of Energy Research, 2026)
In recent years, the pursuit of sustainable energy sources and concerns about the environmental impacts of fossil fuels have driven the growth of photovoltaic solar energy in Brazil, which stands out as a promising alternative in the global energy scenario. Considering the need for monitoring and maintenance of solar plants, it becomes essential to understand how the efficiency and performance of these installations evolve over time. In this context, the present study carried out a ten-year analysis of the efficiency and performance of a photovoltaic plant installed in 2013 at the Mossoró campus of UFERSA, with a power of 3.43 kWp, consisting of 14 modules of 245 Wp connected in a single string. The methodology involved collecting and comparing the main electrical parameters of the plant, such as voltage, current, power, total harmonic distortion (THD), and power factor, evaluating data obtained over ten years of operation. The main objective of the work was to quantify losses and identify trends of system degradation, aiming to indicate necessary interventions to mitigate losses and improve the efficiency of the photovoltaic system. As results, gradual reductions in efficiency and changes in the analyzed parameters were observed throughout the studied period, associated with factors such as dirt accumulation, shading, and natural degradation of the modules. Continuous monitoring and the adoption of preventive maintenance practices proved essential to correct deviations and ensure the best system performance over time